Sex pheromone of a coccoid insect with sexual and asexual lineages: fate of an ancestrally essential sexual signal in parthenogenetic females. Issue 128 (1st March 2017) - Tabata, Jun; Ichiki, Ryoko T.; Moromizato, Chie; Mori, Kenji
Abstract : Sex pheromones play a central role in intersexual communication for reproduction in many organisms. Particularly in insects, reproductive isolation that leads to speciation is often achieved by shifts of pheromone chemistries. However, the divergence and evolution of pheromones remain largely unknown. This study reveals a unique evolutionary consequence for terpenoid pheromones in coccoid insects. Coccoids, such as mealybugs, show clear sexual dimorphism: males are dwarf and short-lived, whereas females are wingless and almost immobile. Female pheromones are therefore indispensable for males to navigate for sexual reproduction, but some females can reproduce asexually. Interestingly, a derived asexual lineage that reproduces by parthenogenesis coexists with its ancestral lineage that reproduces sexually in a population of the pineapple mealybug, Dysmicoccus brevipes . Here, we isolated, characterized and synthesized a novel monoterpene, (−)-( anti -1, 2-dimethyl-3-methylenecyclopentyl)acetaldehyde, as a pheromone of the sexual females of D . brevipes . This monoterpene aldehyde, with an irregular linkage of isoprene units, is notable, because all mealybug pheromones previously reported are carboxylic esters of terpenols. This compound was, however, never produced by the asexual females. As a consequence of acquiring parthenogenetic reproduction, the asexual females appear to have abandoned the production of the sex pheromone, which had been essential to attracting males in their ancestors.